Структура та енергетика утворення багатократно протонованих молекулярних іонів акридинового жовтого: квантовохімічні розрахунки - Demianenko, E. M.; Grebenyuk, A. G.; Lobanov, V. V.; Gabovich, V. O.; Pokrovskiy, V. O.; Terets, M. I. (Chuiko Institute of Surface Chemistry National Academy of Sciences of Ukraine, 2016)
Density functional theory method with functional B3LYP and basis set 6-31G (d,p) has been used to examine the possible structures of acridine yellow fragments resulting from laser irradiation of acridine yellow adsorbed on the surface of expanded graphite under mass spectrometric experiment. The structures of these fragments have been found as well as thermodynamic parameters of the transformation products of the acridine yellow molecule.